Audit committee attributes and the reporting timeliness of listed Nigerian firms - Gloria Okeoghene Odjaremu; Edirin Jeroh (Trends Economics and Management, 2019)
Purpose of the article: This study appraised the extent to which audit committee attributes influence the reporting timeliness of listed Nigerian firms. In this light, firm level secondary data were sourced from the financials of 21 randomly selected firms over a 6 year period (2012-2017). Methodology/methods: The ex-post facto research design was the methodological basis of this research. Additionally, both descriptive and inferential statistical techniques were employed to practically analyse the collated data. Diagnostics tests used included the VIF and Breusch Pagan tests and the study's hypothesis was developed and tested at 0.05 significance level by means of regression analysis. Scientific aim: This research aims to analyse the link between the attributes of audit committees of firms (size, independence and diligence) and the timeliness of financial reporting by obtaining empirical evidence from listed corporate entities in Nigeria. Findings: The results indicate that audit committee attributes (measured by size, independence and diligence) had a significant relationship with financial reporting timeliness among firms in Nigeria. Conclusion: Since the size, independence and diligence of the audit committee was found to have significant influence on the reporting timeliness of firms, we therefore recommend that while firms are continuously monitored to strictly adhere to the guidelines and present stipulated threshold in constituting their respective audit committees; conscious efforts must be made by regulatory bodies to also monitor the compliance levels of firms especially with respect to the level of independence and diligence of the audit committees.
Keywords: G34; M40; M41; 650; audit quality; audit; financial reporting; Nigeria; audit diligence; corporate governance